Climatic control and population dynamics of black grouse (Tetrao tetrix) in the Western Italian Alps. Issue 1 (4th December 2014) - Viterbi, Ramona; Imperio, Simona; Alpe, Dante; Bosser‐peverelli, Vittorio; Provenzale, Antonello
ABSTRACT The analysis of density fluctuations of key species is a crucial element for assessing how natural ecosystems respond to climate and environmental change. The black grouse (Tetrao tetrix) has experienced a constant population decline in the recent decades in Italy. We investigated whether meteorological variables and density dependence affected the growth rate of a black grouse population in the Orsiera‐Rocciavrè Park (Piedmont, Italy) in the western Alps from 1991–2009. Empirical models showed that population growth rates were negatively affected by rainfall during the brooding–hatching period (early Jun) and were positively influenced by the diurnal temperature variation during the snow‐burrowing period (Dec). We then used the most parsimonious models derived from the data to project black grouse population estimates (2010–2050) based on published regional and global climate models. In most cases, the population remained rather stable or weakly decreased in future climate scenarios, both with and without the inclusion of density‐dependent effects, but it displayed significant oscillations depending upon the vagaries of the climate. The influence of meteorological variables in regulating black grouse population dynamics indicated that management actions should consider the climatic conditions affecting the population. In particular, the conservation of breeding and wintering habitats should be promoted by limiting human disturbances and reducing hunting quotas in years with unfavorable weather conditions. © 2014 The Wildlife Society.